Pokoly József - Csohány, János (Gerundium, 2015)
JÓZSEF POKOLY REKTOR. After inishing theology studies, he was the tutor of Count Lajos Tisza (son of Prime Minister Kálmán Tisza) in Geszten, then he was a Reformist priest for a year. He was the teacher of church history at the Reformist heology Academy in Kolozsvár from 1895, and at the heology Academy of the Debrecen Reformist College from 1912. At the University of Debrecen, established in 1914, he became the professor of ancient history at the Faculty of Arts from 1918 on. Between 1922 and 1930, until his retirement, he was the teacher of church history at the Faculty of Reformist heology. During the academic year of 1920–21 he was the Rector of the University. Until his retirement, he was the President of the István Tisza Scientiic Society and he also worked as a senate member of the University. His worked centered around Reformist church history and the history of Hungarian Protestantism in 16–17th centuries.